Hubungan Obesitas Berdasarkan Indeks Massa Tubuh dengan Kadar Proteinuria pada Wanita Hamil Rentang Usia 20-29 Tahun - Nabilla Calulla; Irfan Darfika Lubis (Universitas Insan Budi Utomo, 2026)
Proteinuria is a condition where there is protein in the urine. Indonesian demographic health survey data has a prevalence of preeclampsia in Indonesia of around 3-10%. Proteinuria is one of the common manifestations of patients with pre-eclampsia (PE). On the other hand, obesity is increasingly recognized as a risk factor for kidney disease and proteinuria levels. This study aims to evaluate the relationship between obesity based on body mass index and proteinuria levels in pregnant women aged 20-29 years in Medan City. The type of research is descriptive analytic with a cross-sectional research design. The sample used in this study was pregnant women aged 20-29 years who were obese in Medan Deli District with a total of 67 respondents. This research was carried out by measuring the respondents' weight, height and proteinuria levels. The measurement results were analyzed using univariate and bivariate tests using the Chi-square test. The majority of pregnant women aged 20-29 years were found to be in the type 1 obesity category with negative proteinuria levels. Meanwhile, the relationship between type 2 obesity and positive proteinuria levels is 1 with a sig value. found 0.001 at the 95% confidence level. There is a significant relationship between type 2 obesity and positive proteinuria in pregnant women.